RNA from Trained Aplysia Can Induce an Epigenetic Engram for Long-Term Sensitization in Untrained Aplysia - Bédécarrats, Alexis (eNeuro, 2018)
The precise nature of the engram, the physical substrate of memory, remains uncertain. Here, it is reported that RNA extracted from the central nervous system of Aplysia given long-term sensitization (LTS) training induced sensitization when injected into untrained animals; furthermore, the RNA-induced sensitization, like training-induced sensitization, required DNA methylation. In cellular experiments, treatment with RNA extracted from trained animals was found to increase excitability in sensory neurons, but not in motor neurons, dissociated from naïve animals. Thus, the behavioral, and a subset of the cellular, modifications characteristic of a form of nonassociative long-term memory (LTM) in Aplysia can be transferred by RNA. These results indicate that RNA is sufficient to generate an engram for LTS in Aplysia and are consistent with the hypothesis that RNA-induced epigenetic changes underlie memory storage in Aplysia.